CHANGE OF SEA SURFACE HEIGHT IN THE SOUTHERN WATERS OF JAWA-SUMBAWA DURING INDIAN OCEAN DIPOLE 2016 - Martono, Martono (Badan Informasi Geospasial, 2017)
Indian Ocean Dipole is a weather deviation that occurs in the tropical Indian Ocean due to air-sea interactions. This study was conducted to understand sea surface height change in the southern waters of Java, Bali and Lombok-Sumbawa during Indian Ocean Dipole 2016 events. Data used consists of dipole mode index, daily sea surface height, monthly chlorophyll-a concentration and pentad geostropic current. Anomaly analysis was used to assess sea surface height change. The result showed that during Indian Ocean Dipole 2016 events occured the increase of sea surface height in these waters. The average increase of sea surface height from June-Novemver 2016 in the southern waters of Java, Bali and Lombok-Sumbawa approximately 25 cm, 23 cm and 17 cm, respectively. Impact of the increase of sea surface height affects chlorophyll-a concentration to drop that was marked by negative anomaly. The highest decrease of chlorophyll-a concentration occured in the southern waters of Java. The decrease of chlorophyll-a concentration in in the southern waters of Java reached -1.02 mg/m3, in the southern waters of Bali reached -0.74 mg/m3 and in the southern waters of Lombok-Sumbawa reached -0.35 mg/m3.Â Keywords: change, sea surface height, Indian Ocean Dipole, chlorophyll-a